Knowledge of community care workers about key family practices in a rural community in South Africa - Ethelwynn Stellenberg; Marjorie van Zyl; Johanna Eygelaar (AOSIS, 2015)
Background: Interventions by community care workers within the context of communitybased integrated management of childhood illness (CIMCI) may have a positive effect on child health if the health workers have adequate knowledge about key family practices. Setting: The study was conducted in rural areas of the West Coast district in the Western Cape, South Africa. Objectives: The objective of this study was to determine the knowledge of community care workers about five of the 16 key family practices of CIMCI. Methods: A descriptive survey collected a self-administered questionnaire from 257 community care workers out of a possible total of 270 (95.2% response rate). Descriptive and inferential statistical analysis was applied. Results: Only 25 of the respondents (10%) obtained a score higher than 70% on the knowledgebased items of the questionnaire. Less than 25% of respondents answered questions in these key areas correctly (pneumonia [17%], tuberculosis [13%], HIV/AIDS [9%] immunisation [3%] and recommendations for a child with fever [21%]). Statistically significant correlations were found between the total score a respondent achieved and the highest level of education obtained (p < 0.01), the level of in-service training (p < 0.01), attendance of a CIMCI five-day training course (p < 0.01), and completing a subsequent refresher course (p < 0.01). Conclusion: The knowledge of CCWs was inadequate to provide safe, quality CIMCI. CIMCI refresher courses should be offered annually to improve CCWs' knowledge and the quality of care that they render. Regular update courses could contribute to building competence.